The The Development of Green Human Resources Management in Indonesia - Endah Kurniawati (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
The environmental damage that occurs due to industrial development requires organizations to implement Green HRM (Human Resource Management) to achieve the company's environmental and sustainability goals, as well as provide benefits for employees and the company. By implementing Green HRM, companies can improve efficiency and environmental performance. This research aims to provide a detailed description of Green HRM practices as additional knowledge and new insights. This research was conducted with a qualitative descriptive approach and used data collection methods through literature studies. The study showed the result that the development of Green HRM in Indonesia has shown progress but still facing many challenges and obstacles. The sustainability and diversity of human resources in Indonesia can be a competitive advantage that strengthens Green HRM practices